Penerapan Metode SAW untuk Perancangan SPK Penerimaan Karyawan Di PT Pinnacle Apparels - Novianto, Sendi; Panca Hutama Caniago; Pulung Nurtantio Andono (Journal on Pustaka Cendekia Informatika, 2023)
A company cannot grow without the support of its employees as one of its pillars. Therefore, the company needs to recruit potential and talented candidates who can contribute to its success. Skilled employees who can help the company grow and compete with the changing times are now receiving special attention, as recruitment processes that do not meet the company's needs can hinder its development. Hence, a decision support system is needed for the employee selection process. This decision support system utilizes the Simple Additive Weighting (SAW) method. Candidates are compared to each other, resulting in a prioritized intensity value that assesses each candidate. This decision support system simplifies the evaluation of each candidate and allows for changes in criteria and weight values. This decision support system is beneficial for facilitating decision-making related to the selection of suitable candidates, ensuring that the company hires the most suitable employees